Combined Intestinal Metabolomics and Microbiota Analysis for Acute Endometritis Induced by Lipopolysaccharide in Mice - Dong, Yuqing; Yuan, Yuan; Ma, Yichuan; Luo, Yuanyue; Zhou, Wenjing; Deng, Xin; Pu, Jingyu; Hu, Binhong; Liu, Songqing (Frontiers in Cellular and Infection Microbiology, 2021)
Endometritis is generally caused by bacterial infections, including both acute and chronic infections. In the past few decades, accumulated evidence showed that the occurrence of diseases might be related to gut microbiota. The progression of diseases is previously known to change the composition and diversity of intestinal microbiota. Additionally, it also causes corresponding changes in metabolites, primarily by affecting the physiological processes of microbiota. However, the effects of acute endometritis on intestinal microbiota and its metabolism remain unknown. Thus, the present study aimed to assess the effects of acute endometritis on intestinal microbes and their metabolites. Briefly, endometritis was induced in 30 specific pathogen-free (SPF) BALB/c female mice via intrauterine administration of lipopolysaccharide (LPS) after anesthesia. Following this, 16S rRNA gene sequencing and liquid chromatogram-mass spectrometry (LC-MS) were performed. At the genus level, the relative abundance of Klebsiella, Lachnoclostridium_5, and Citrobacter was found to be greater in the LPS group than in the control group. Importantly, the control group exhibited a higher ratio of Christensenellaceae_R−7_group and Parasutterella. Furthermore, intestinal metabolomics analysis in mice showed that acute endometritis altered the concentration of intestinal metabolites and affected biological oxidation, energy metabolism, and biosynthesis of primary bile acids. The correlation analysis between microbial diversity and metabolome provided a basis for a comprehensive understanding of the composition and function of the microbial community. Altogether, the findings of this study would be helpful in the prevention and treatment of acute endometritis in the future.